Validity and reliability of force-time characteristics using a portable load cell for the isometric midthigh pull - Pichardo, A. W.; Neville, J.; Tinwala, F.; Cronin, J. B.; Brown, S. R. (The Journal of Strength and Conditioning Research, 2024)
Many practitioners use the isometric midthigh pull (IMTP) to assess maximal strength in a safe, time-effective manner. However, expensive, stationary force plates are not always practical in a large team setting. Therefore, the purpose of this study was to establish the validity and between-session reliability of peak force, rate of force development (RFD), and impulse during an IMTP using 2 experimental protocols: a traditional fixed bar with a force plate (BarFP) and a flexible chain measured with a force plate (ChainFP) and a load cell (ChainLC). After a familiarization session, 13 resistance-trained men performed 3 trials of the BarFP condition and 3 trials of the chain-based conditions. The identical procedures were replicated twice more, with a week between each testing session. The main findings were (a) no RFD or impulse measures were found to achieve acceptable reliability across all methodological approaches and testing occasions; (b) peak force was reliable across all methods, with coefficient of variation ranging from 4.6 to 8.3%, intraclass correlation coefficient ranging from 0.94 to 0.98, and the least variability associated with the ChainLC condition; and (c) the ChainFP method was found to significantly underrepresent peak force by 4.8% (p < 0.05), with no significant differences between the ChainLC and BarFP methods. Therefore, the ChainLC would seem a valid, reliable, portable, and cost-effective alternative to force plates when assessing maximal isometric strength in the IMTP.